Spatially-averaged momentum fluxes and stresses in flows over mobile granular beds: a DNS-based study. Issue 2 (4th March 2017) - Vowinckel, Bernhard; Nikora, Vladimir; Kempe, Tobias; Fröhlich, Jochen
ABSTRACT: Based on direct numerical simulations, the paper investigates momentum fluxes and hydrodynamic stresses within and above a mobile granular bed in a turbulent open-channel flow laden with monodisperse spherical particles. Two simulation scenarios are considered: one with partially mobilized particles ("heavy" particles) and another with all particles in motion ("light" particles). The momentum fluxes were computed as temporal and spatial averages following the double-averaging methodology for rough-bed flows. The analysis, hence, allows the DNS data to be convoluted in a rigorous way to provide detailed description and quantification of the physical mechanisms involved in momentum exchanges. In particular, it was found that heavy particles create streamwise bedforms causing heterogeneity in the spanwise direction. This yields significant form-induced momentum fluxes that cannot be neglected. For both scenarios, the mobile particles take up a substantial amount of the momentum supplied, which ultimately increases the hydraulic resistance of the channel. These effects enhance and stabilize secondary flows in the channel.